MANAJEMEN STRATEGI DALAM MENGEMBANGKAN KUALITAS SUMBER DAYA MANUSIA DI LEMBAGA PENDIDIKAN - Istiqlal Widyatama Ihsan Fasya; Sulistyorini; Chusnul Chotimah (STISIP Widyapuri Mandiri, 2026)
Islamic education plays a vital role in raising quality offspring with good morals; therefore, schools must be firmly committed to providing proper education and have qualified human resources capable of fulfilling their obligations. In the current era of globalization, improving the quality of human resources in schools is crucial. How is strategic management planning used in developing the quality of human resources in educational institutions? How is strategic management implemented in developing the quality of human resources in educational institutions? How is strategic management evaluation used in developing the quality of human resources in educational institutions? This research can also benefit principals, teachers, and other education personnel, as well as support further research on strategic management to improve the quality of human resources in Islamic educational institutions. This study uses a literature review to examine references on strategies to improve the quality of human resources in Islamic schools—training, internships, scholarships, and prizes; increasing human resource welfare; and collaborating with other parties. Performance evaluation assessments are carried out by superiors or foundation owners and the principal in private schools, while in public schools, it is the principal and the school committee.